COMMODITY CONCENTRATION OF LIBYAN TRADE - المهدی , عطيه (Dirasat in Economics and Business, 1977)
The purpose of this paper is to investigate the trends in the commodity concentration of the Libyan imports and export. This aspect is of interest in studying the patterns of economic development since the degree of commodity concentration tends to vary with economic development and the size of the economy.